IMPLEMENTATION OF AN ECOPEDAGOGIC APPROACH IN THE HISTORY SUBJECT OF THE INDEPENDENT CURRICULUM - Mardiani, Fitri; Hermawan, M. Dody; Halim, Abdul; Maulidi, Said (International Conference On Social Science Education, 2023)
History subjects are central in shaping individuals' understanding of past events and today's and future projections regarding their impact on environmental issues. Ecopedagogics, a concept combining ecology and education, becomes an actual framework relevant for introducing environmental issues in history learning. The literature study was used as a method in this study as researchers mapped sources from books and research results published in articles whose studies were related to history learning and ecopedagogical approaches in history learning. Ecopedagogy in history learning can develop a critical awareness of environmental issues and encourage students to be responsible for nature. Through an ecopedagogic approach to learning history, students learn about the history and become agents of change responsible for environmental preservation and future sustainability.